2015
DOI: 10.1590/0104-1169.0350.2632
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Brucella spp in humans

Abstract: Objective: to determine the seroprevalence of Brucella spp in humans.Method: this is an observational study, developed with 455 individuals between 18 and 64 years old, who use the Estratégia de Saúde da Família (Brazil's family health strategy). The serum samples of volunteers underwent buffered acid antigen tests, such as screening, agar gel immunodiffusion and slow seroagglutination test in tubes and 2-Mercaptoethanol. Results: among the samples, 1.98% has responded to buffered-acid antigen, 2.85% to agar g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
1
12
2
8
Order By: Relevance
“…There has been extensive scientific research that has shown a wide range of zoonotic infections, which are caused by different strains of Brucella ( 31 34 ). The identification of these bacteria can be very critical in the medical society ( 35 ). Because of some antibiotic-resistant genes, the prevalence of Brucellosis is increasing, and, as a result, it is necessary to develop a rapid identification technique that can replace culture and biochemical tests.…”
Section: Resultsmentioning
confidence: 99%
“…There has been extensive scientific research that has shown a wide range of zoonotic infections, which are caused by different strains of Brucella ( 31 34 ). The identification of these bacteria can be very critical in the medical society ( 35 ). Because of some antibiotic-resistant genes, the prevalence of Brucellosis is increasing, and, as a result, it is necessary to develop a rapid identification technique that can replace culture and biochemical tests.…”
Section: Resultsmentioning
confidence: 99%
“…Respecto a este último factor, el consumo de lácteos no pasteurizados continúa siendo una de las principales causas de infección (Swai & Schooman 2009;Yoo et al 2009;Cavalcanti et al 2015;Mufinda et al 2017;Acharya et al 2018). A pesar de que, en el área de estudio, la práctica de consumir productos lácteos sin pasteurizar es muy frecuente y es un importante factor de riesgo, se considera importante hacer notar que el consumo de leche, que se esperaba fuera un factor de riesgo, no lo es (Cavalcanti et al 2015). Esto se explica en que, en los hogares de los encuestados, la leche suele ser hervida para el consumo en su forma fluida, más no para la producción de quesos artesanales, helados, yogurt u otros.…”
Section: Discussionunclassified
“…(PESSEGUEIRO et al, 2003). This genus presents ten species that have as their preferential hosts: Brucella microti (infects field mice), Brucella inopinata (infects humans), Brucella abortus (infects cattle), Brucella pinnipedialis (infects marine mammals that alternate their habitat between sea and land, for example, walrus and seals), Brucella melitensis (infects goats), Brucella suis (infects reindeer, pigs, hares, and rodents), Brucella ceti (infects cetaceans), Brucella ovis (infects sheep), Brucella neotomae (infects desert rats), and Brucella canis (infects dogs) (SOARES et al, 2015).…”
Section: Seroprevalence Of Ovine Brucellosis In the Microregion Of Tementioning
confidence: 99%